Design and realization of a novel haptic graspable interface for augmenting touch sensations - Pediredla, Vijay Kumar; Chandrasekaran, Karthik; Annamraju, Srikar; Thondiyath, Asokan (Frontiers in Robotics and AI, 2022)
A novel haptic grasper that renders touch sensations to the user in 3-DoF, namely linear, rotary, and grasping motions, is presented. The touch sensations of the grasper include the combination of kinesthetic and tactile modalities such as stiffness, texture, and shape. The device is equipped with two swappable modular segments that provide stiffness and shape sensations. To increase the haptic fidelity, the textural surfaces that surround the outer surface of the segments are equipped with vibro-actuators underneath them. These vibro-actuators contribute to increasing the number of perceivable textures by varying amplitude, frequency, duration, and envelope of vibrations. The proposed device is characterized in terms of stiffness, shape and texture rendering capabilities. The experimental results validate the effectiveness of the developed haptic grasper in virtual/remote interactions. Also, the user studies and statistical analysis demonstrate that the users could perceive the high-fidelity haptic feedback with the unified sensations of kinesthetic and tactile cues.